Most ardently : a Pride & prejudice remix - Novoa, Gabe Cole (Remixed classics., 2024)
London, 1812. Oliver Bennet feels trapped. Not just by the endless corsets, petticoats and skirts he's forced to wear on a daily basis, but also by society's expectations. The world--and the vast majority of his family and friends--think Oliver is a girl named Elizabeth. He is therefore expected to mingle at balls wearing a pretty dress, entertain suitors regardless of his interest in them, and ultimately become someone's wife. But Oliver can't bear the thought of such a fate. He finds solace in the few times he can sneak out of his family's home and explore the city rightfully dressed as a young gentleman. It's during one such excursion when Oliver becomes acquainted with Darcy, a sulky young man who had been rude to "Elizabeth" at a recent social function. But in the comfort of being out of the public eye, Oliver comes to find that Darcy is actually a sweet, intelligent boy with a warm heart. And not to mention incredibly attractive. As Oliver is able to spend more time as his true self, often with Darcy, part of him dares begin to hope that his dream of love and life as a man could be possible. But suitors are growing bolder--and even threatening--and his mother is growing more desperate to see him settled into an engagement. Oliver will have to choose: Settle for safety, security, and a life of pretending to be something he's not, or risk it all for a slim chance at freedom, love, and a life that can be truly, honestly his own.